Role Of Music In Farmers’ Protest: A Study - Kaur, Navpreet (The journal of contemporary issues in business and government, 2021)
Music is considered as one of the oldest forms of expression. It is a universal language which is always used by the educators, students, activists as a way of community protest against the governments or the authorities. Protesting through the music has become one of the media where people chooses musical notes as a way be vocal and loud for the oppression. A way of reaching people at large and where people can be educated, informed, motivated and to raise consciousness both emotionally and intellectually. The music is a way of bringing social change and social justice to the society at large. The paper aims to understand the ability of the music in the on going farmer’s protest in Delhi against the Centre Government for the New Agriculture bill.